Solve for y 2(y+2)+y=3(y-1)+6

Math
2(y+2)+y=3(y-1)+6
Simplify 2(y+2)+y.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
2y+2⋅2+y=3(y-1)+6
Multiply 2 by 2.
2y+4+y=3(y-1)+6
2y+4+y=3(y-1)+6
Add 2y and y.
3y+4=3(y-1)+6
3y+4=3(y-1)+6
Simplify 3(y-1)+6.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
3y+4=3y+3⋅-1+6
Multiply 3 by -1.
3y+4=3y-3+6
3y+4=3y-3+6
Add -3 and 6.
3y+4=3y+3
3y+4=3y+3
Move all terms containing y to the left side of the equation.
Tap for more steps…
Subtract 3y from both sides of the equation.
3y+4-3y=3
Combine the opposite terms in 3y+4-3y.
Tap for more steps…
Subtract 3y from 3y.
0+4=3
Add 0 and 4.
4=3
4=3
4=3
Since 4≠3, there are no solutions.
No solution
Solve for y 2(y+2)+y=3(y-1)+6

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top